Factors associated with inspiratory muscle weakness in patients with HIV-1 - Jerônimo,Fabiana S. (2015)
Background:the impact of human immunodeﬁciency virus type 1 (HIV-1) on lung function is well known and associated with a reduction in pulmonary ventilation. Moreover, the use of highly active antiretroviral therapy has been associated with mitochondrial dysfunction and decreased muscle strength. However, there is scarce information about the factors associated with inspiratory muscle weakness in these patients.Objective:the purpose of the present study was to investigate the factors associated with inspiratory muscle weakness in patients with HIV-1.Methods:two-hundred ﬁfty seven patients with HIV-1 were screened and categorized into two groups: (1) IMW+ (n= 142) and (2) IMW-(n= 115). Lung function (FEV1, FVC and FEV1 /FVC), maximum inspiratory pressure, distance on the six-minute walk test and CD4 cell count were assessed.Results:the mean duration of HIV infection was similar in the two groups. The following variables were signiﬁcantly different between groups: mean duration of highly active antiretroviral therapy (81 ± 12 in IMW+ versus 38 ± 13 months in IMW-; p= 0.01), and CD4 cell count (327 ± 88 in IMW+ versus 637 ± 97 cells/mm3 in IMW-; p= 0.02). IMW+ presented reduced lung function (FEV1, FVC, FEV1/FVC).Conclusion:patients with IMW+ had lower distance on the six-minute walk test in comparison to the IMW- group. The duration of highly active antiretroviral therapy, distance traveled on the 6MWT and CD4 count were determinants of IMW in patients with HIV.